2023
DOI: 10.1002/mar.21824
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the flow experience in apps: Fostering long‐term adoption for sustainable healthcare systems

Abstract: Mobile health apps are increasingly being recognized as effective tools for improving the efficiency and sustainability of healthcare systems. However, a major challenge faced by the industry is achieving long-term adoption of Apps. This is a critical issue because many apps are abandoned after only a few uses, and low adoption rates limit the potential impact of these apps on healthcare outcomes. In this paper, we examine this issue by integrating the Customer Value Theory and the Person-Artifact-Task model t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 104 publications
(254 reference statements)
0
0
0
Order By: Relevance
“…This interpretation is also supported by the literature on motivations for exercise that has suggested that social interaction with others is the main motivation for participation in exercise and physical activities [60][61][62]. Furthermore, as numerous studies have suggested that flow experience is a barometer and enhancer of the quality of a target task and thus is a powerful predictor of adherence to the task [25][26][27][28]39,[41][42][43][44]63,64], our study also found that both absorption and enjoyment (flow experience) positively affected exercise intention with smartwatches (H6). In other words, the more flow state an individual experiences during exercise with a smartwatch, the more likely he or she is to participate in and adhere to exercise and physical activities with the smartwatch.…”
Section: Interpretations Of Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…This interpretation is also supported by the literature on motivations for exercise that has suggested that social interaction with others is the main motivation for participation in exercise and physical activities [60][61][62]. Furthermore, as numerous studies have suggested that flow experience is a barometer and enhancer of the quality of a target task and thus is a powerful predictor of adherence to the task [25][26][27][28]39,[41][42][43][44]63,64], our study also found that both absorption and enjoyment (flow experience) positively affected exercise intention with smartwatches (H6). In other words, the more flow state an individual experiences during exercise with a smartwatch, the more likely he or she is to participate in and adhere to exercise and physical activities with the smartwatch.…”
Section: Interpretations Of Resultsmentioning
confidence: 60%
“…The importance of flow experience has been highlighted in a wide range of contexts because it is strongly related to positive outcomes of exercise, including exercise satisfaction and intrinsic rewards, performance enhancement, health-related quality of life, perceived health improvement, mental health, well-being, and adherence to physical activities and exercise, among others [25][26][27][28][41][42][43][44]. Among these benefits of flow experience, in particular, the current study focused on the relationship between flow experience and intention to continuously engage in exercise using smartwatches due to its theoretical and practical implications in the field of healthcare.…”
Section: Introductionmentioning
confidence: 99%